Guanidinoacetic acid attenuates high-fat diet induced colitis by targeting mitophagy and the gut microbiota in middle-aged mice - Zhao, Jiamin; Ji, Bingzhen; Li, Xvying; Zhang, Weipeng; Zhao, Junxing (Food bioscience, 2025)
The increasing incidence of obesity has been associated with various diseases, including inflammatory bowel disease. Guanidinoacetic acid (GAA) regulated various crucial physiological processes. The present study aimed to determine the action of dietary GAA on high-fat diet (HFD)-induced colitis in middle-aged mice. Mice (8 months old) were fed chow or HFD with or without GAA (1 %). These results suggested that dietary GAA effectively prevented HFD-induced obesity, colon shortening, and morphological changes in the colon. Moreover, GAA intake reduced abundances of pro-inflammatory chemokines, including tumor necrosis factor-α interleukin-1β and interleukin-6, and inhibited the activation of nuclear factor kappa B (NFκB) and inhibitor of kappa B (IκB) in the colon of HFD-induced obese mice. GAA supplementation restored the declined expression of intestinal tight junction proteins, including claudin 1 and zonula occludens-1 (Zo1), in HFD-induced obese mice, and upregulated the expression of mitophagy-related proteins, including microtubule-associated protein 1A/1B-light chain 3, phosphatase and tensin homologue-induced kinase 1 and parkin. Furthermore, the regulatory effect of GAA supplementation on intestinal tight junction protein expression (claudin 1 and Zo1) and inflammation response (phosphor-NFκB and phosphor-IκB) in Mode-K cells were attenuated when cells were treated with Mdivi-1, an inhibitor of mitophagy. Additionally, dietary GAA altered the diversity and relative abundance of the colonic flora. Jointly, these data suggest that dietary GAA alleviates HFD-induced colitis and inflammation by activating mitophagy and affecting the composition of the colonic flora. [Display omitted]